Should the Start of Immunosuppressive Treatment for COVID-19 Rely upon the Degree of Inflammation or the Time from Onset? - José María Mora-Luján; Abelardo Montero; Francesc Formiga; Manuel Rubio-Rivas (Medicina)
Background and Objectives: A COVID-19 model with a viral first-week phase and an inflammatory second phase has been proposed. It has been suggested that immunosuppressive treatment in the first week is harmful. This study aimed to analyze the potential damage of corticosteroids (CS) administered in the first week of COVID-19. Materials and Methods: This study was performed on a large cohort of consecutive COVID-19 patients admitted to Bellvitge University Hospital (Barcelona, Spain) from March 2020 to April 2021. Patients diagnosed with COVID-19 who were treated with 6 mg of dexamethasone a day for 10 days, and whose initiation of administration occurred within the first 2 weeks from symptom onset were included. We divided the cohort into the following two groups: patients for whom CS were initiated within the first 7 days after symptom onset vs. patients for whom CS were initiated between days 8 and 14. The degree of analytical inflammation (based on lymphocyte count, C-reactive protein, ferritin, lactate dehydrogenase, and D-dimer) upon admission was taken into account. The primary outcome was in-hospital mortality. Results: A total of 581 patients met the inclusion criteria. The results included, as follows: differences in age at baseline between groups (70.8 years old vs. 62.7, p < 0.001); moderate-to-severe dependency (11.9% vs. 4.2%, p = 0.003); the lymphocyte count (840 × 106/L vs. 900, p = 0.033); D-dimer (400 ng/mL vs. 309, p < 0.001); and PaO2/FiO2 (290 vs. 311, p < 0.001). In-hospital mortality in patients who received CS in the first week of symptom onset was higher (29% vs. 12.8%, p < 0.001). The following risk factors were associated with higher in-hospital mortality: age (OR = 1.06, p < 0.001); Charlson index (OR = 1.34, p = 0.001); tachypnea > 20 bpm (OR = 2.58, p < 0.001); ≥3 high-risk criteria of inflammation (OR = 1.94, p = 0.012); and CS onset in the first week (OR = 2.17, p = 0.004). A higher PaO2/FiO2 (OR = 0.99, p < 0.001) and the use of remdesivir (OR = 0.53, p = 0.021) were identified as protective factors. However, when stratified by analytical inflammation criteria, the onset of CS in the first week did not reach statistical significance. Conclusions: The early administration of CS did not demonstrate a significant detrimental effect. These results highlight the need for a nuanced approach to CS therapy in COVID-19 that carefully weighs the risks and benefits based on individual patient characteristics and the severity of the inflammation.